Implantable cardioverter‐defibrillator in Brugada syndrome: Long‐term follow‐up. Issue 10 (22nd August 2019) - El‐Battrawy, Ibrahim; Roterberg, Gretje; Liebe, Volker; Ansari, Uzair; Lang, Siegfried; Zhou, Xiaobo; Borggrefe, Martin; Akin, Ibrahim
Abstract: Background: Brugada syndrome (BrS) is associated with sudden cardiac death (SCD). Although implantable cardioverter‐defibrillator (ICD) implantation is recommended, the long‐term outcomes and follow‐up data with regard to ICD complications have led to controversy. Hypothesis: In the present study, we described the data assimilated in a total of 11 studies, analyzing the outcome in 747 BrS patients receiving ICD. Methods: Data were performed and analyzed after a systematic review of literature compiled from a thorough database search (PubMed, Web of Science, Cochrane Library, and Cinahl). Results: The mean age of patients receiving ICD was (43.1 ± 13.4, 82.5% males, 46.6% spontaneous BrS type I). Around 15.3% of the patients were admitted due to SCD and 10.4% suffered from atrial arrhythmia. Appropriate shocks were documented in 18.1% of the patients over a mean follow‐up period of 82.3 months (47.5‐110.4). The following complications were recorded: lead failure and fracture (5.4%), lead perforation (0.7%), lead dislodgement (1.7%), infection (3.9%), pain (0.4%), subclavian vein thrombosis (0.3%), pericardial effusion (0.1%), endocarditis (0.1%), psychiatric problems (1.5%), pneumothorax (0.7%). Inappropriate shocks were documented in 18.1% of the patients. The management of inappropriate shocks was achieved by pulmonary vein isolation (0.5%), drug treatment with sotalol (1.3%) or sotalol with beta‐blocker (0.3%) and hydroquinidine (0.1%). Conclusions: ICD therapy in BrS is associated with relevant ICD‐related complications including a substantial risk of inappropriate shocks more frequently in symptomatic BrS patients.